THE STUDENTS’ SPEAKING ANXIETY ON THE YOUTUBE VIDEO PROJECT IN EFL LEARNING IN INDONESIA - Angela Bayu Pertama Sari; Dwi Iswahyuni (Premise: Journal of English Education and Applied Linguistics, 2019)
This research aimed to portray the occurrence of anxiety in the YouTube video project conducted by non-English students. It was descriptive-qualitative research. One hundred twenty-four students participated in this research. The research findings showed that 65 students felt the anxiety, and 59 were not anxious in doing the YouTube video project. There was a slight difference between those two findings. Some factors influenced the students’ anxiety, namely students’ low personal perception, peers’ negative judgment, and quite intimidating learning environment. While the factors that support the absence of anxiety were students’ positive own perception and fun-less intimidating and encouraging learning environment. However, the research finding highlighted that YouTube video project was the preferable media that was based on the 104 students’ responses claiming that they prefer doing YouTube video project than other speaking activities such as storytelling, oral presentation, and speech.